Evaluating the effectiveness of curriculum implementation and supplementation program in a private medical college in south India - Mutalik, Anirudh V.; Ramanathan, Rashmi; Narayanan, Seetharaman; Shanmugam, Jeevithan; Subramanian, Bhuvaneshwari; Mariappan, Karthikeyan Thangappa; Ramalingam, Vijay; Mani, Vijaianand; Shanmugham, Thiriveni Balajji Ganapathy (International Journal Of Community Medicine And Public Health, 2022)
Background: The new competency based medical curriculum was introduced in India from 2019. The curriculum implementation support program (CISP) developed by medical council of India, provides the much-needed intellectual support to colleges for smooth transition from existing to the new curriculum. This study was done to assess the effectiveness of CISP program by comparing the pretest and posttest questionnaire. Methods: This retrospective cross-sectional study was conducted among 30 medical teachers in a medical college after getting Institutional Ethical committee clearance. During the CISP training program, a structured and validated questionnaire were administered, and it was evaluated and compared before and after the workshop. Results: There was a significant improvement in the knowledge of electives, meaning of curriculum, knowledge on curriculum delivery process, knowledge concepts of Miller’s pyramid, hardens integration ladder, GMER and the concepts of SLO. Though there is a significant improvement, the knowledge gained on foundation course, Miller’s pyramid and GMER are still poor (mean score <0.7). Conclusions: The CISP program serves as an effective program to bridge the inadequacies of the teaching faculty regarding the implementation of the new CBME curriculum. But not just one session will tide over all the antiquities. A repeated longitudinal structured program in between the academic hours for a short duration will be effective in improving the teaching skills of the medical teachers.